Mechanical properties of SAC-ECC reinforced with fiber-reinforced polymer mesh. (15th August 2022) - Li, Weiwen; Zhao, Jiali; Huang, Xinlin; Zheng, Jing; Shi, Tiansheng; Shumuye, Eskinder Desta
Highlights: The addition of FRP effectively improves the tensile stiffness and ultimate load of the composite layer in the strain hardening stage. Fracture failure of FRP occurs earlier than that of ECC. SAC-ECC does not lose its strength due to the bridging effect between fiber and matrix and the ultimate stress of FRP-ECC composite layer is relatively high. Composite layer is not damaged by peeling from the bottom of the beam, making full use of the composite layer. Abstract: Fiber-reinforced polymer (FRP) is widely used in the repair and strengthening of concrete structures, owing to its high strength-to-weight ratio, excellent mechanical properties, and good durability. However, during the application of FRP, an organic resin is typically used as the binder between the FRP and concrete, which leads to poor bonding, peeling, and poor high-temperature resistance. The emergence of engineered cementitious composites (ECCs) solves these problems and improves the ductility of the structure. However, most materials must be maintained for an extended period before use, which is not conducive to projects that require rapid repair. Therefore, this study proposes a high-early-strength and high-efficiency composite repair and reinforcement layer, and an ECC based on sulfoaluminate cement and FRP mesh (FRP-ECC(S)) has been developed. Uniaxial tensile tests and four-point bending tests were performed to study the mechanical properties and strengthening effects of the composite plate. The effects of carbon-fiber mesh, mesh size, mesh reinforcement rate, different matrices, and age on the failure mode, crack, stress–strain, and load deflection of composite plates and strengthened beams are discussed. The results showed that the composite plate has excellent mechanical properties, and the FRP-ECC reinforced layer has a significant effect on controlling the crack development of the reinforced concrete beam. In addition, the cast-in-place composite layer did not peel from the bottom of the beam, which improves the durability of the structure.